Case report of surgical treatment of scoliosis caused by neurofibroma located posterior mediastinum. (2018) - Motono, Nozomu; Kawaguchi, Masahito; Kawahara, Norio; Uramoto, Hidetaka
Highlights: Neurofibromatosis type 1 (NF-1) is often associated with various orthopedic disorders, especially scoliosis. Spinal deformity in patients with NF-1 can be induced by localized neurofibromas. The optimum surgical approach for the release of neurofibroma located in the posterior mediastinal remains to be established. We safety performed a two-stage procedure involving the release of a neurofibroma in the lateral position/extirpation of the neurofibroma and posterior spinal fusion with segmental spinal instrumentation for scoliosis in the prone position. Abstract: Background: Neurofibromatosis type 1 (NF-1) is often associated with various orthopedic disorders, especially scoliosis. Spinal deformity in patients with NF-1 can be induced by localized neurofibromas. Case presentation: Scoliosis can be induced by a localized neurofibroma. A 12-year-old boy diagnosed with neurofibromatosis type 1 had severe scoliosis caused by a neurofibroma located in the posterior mediastinum. We performed two-stage procedure involving the extirpation of the neurofibroma in the lateral position, and posterior spinal fusion with segmental spinal instrumentation for the scoliosis in the prone position. Discussion: The optimum surgical approach for the extirpation of neurofibroma located in the posterior mediastinal remains to be established. It may be difficult to extirpate a tumor in this position via a posterior approach alone, as the tumor is surrounded by several tissue, e.g. azygos vein, trachea and esophagus. In our case, we first extirpated the tumor located in the posterior mediastinum via a posterolateral incision in the right lateral position. With this approach, it may be easy to confirm the safe relationship between the tumor and surrounding tissue. Conclusions: We safely performed a two-stage procedure involving the extirpation of a neurofibroma in the lateral position, and posterior spinal fusion with segmental spinal instrumentation for scoliosis in the prone position.